Harmonized System: Binding Pre-entry Information on Customs Classifi cation - Carsten Weerth (Global Trade and Customs Journal, 2008)
More than 200 countries and economic regions worldwide are using the nomenclature of the Harmonized Commodity Description and Coding System (Harmonized System Convention: HS) and basing customs tariffs thereon. The number of HS headings (four-digit code) and HS subheadings (six-digit code) is altered every four to six years, when the nomenclature is revised and updated due to trade patterns and technical development (HS 1988, HS 1992, HS 1996, HS 2002, HS 2007). The World Customs Organization (WCO) has recommended the introduction of programmes for binding pre-entry customs classifi cation information in national customs legislation in order to provide secure information on classification issues and tariff rates for economic operators and customs authorities. This article examines the introduction of binding pre-entry classifi cation information within the HS contracting parties.
Additional information: Storage of Proofs according to the ROMEO-webentry of publisher.
Keywords: K33; K34; 330; Customs Classification; Tariff Classification; Harmonized System